A methodological turn in RE - Aukland, Knut (British Journal of religious education, 2024)
In this article, I make the case for a methodological turn in the field based on the growing interest in a methodology-oriented RE. That is, the idea that we should make academic methods and methodology not just a part of, but part and parcel of the core of teaching about religion and worldviews in public education. This interest is found in research articles, new RE curricula and debates about them, and concrete approaches and teaching materials. The article has three sections. In the first I bring these different contributions from England, Norway and Switzerland together, highlighting key terms and conceptualisations. In the second, I present eight arguments in support of a methodology-oriented RE. In the third, I discuss three questions raised by a methodological turn in the field: (1) How do we translate academic methods into the classroom? (2) How should we think about the relationship between traditional knowledge acquisition and exploration with different methods? (3) What methods should we prioritise, and why?